USABILITY EVALUATION OF COMPUTER-BASED TEST (CBT) SYSTEMS USING SERVQUAL METHODS, GAP ANALYSIS, AND IPA MODELS (Case Study: Dr. Soetomo High School Surabaya): EVALUASI USABILITY SISTEM COMPUTER-BASED TEST (CBT) MENGGUNAKAN METODE SERVQUAL, GAP ANALYSIS, DAN IPA MODEL (Studi Kasus: SMA Dr. Soetomo Surabaya) - Yanti, Risma Novi; Indriyanti, Aries Dwi (Universitas Negeri Surabaya, 2023)
The Computer-Based Test (CBT) is a test conducted using computerized technology that makes it easy for teachers and students to take grades. Dr. High School Soetomo Surabaya is one of the schools that uses CBT technology to support the grade taking process. However, the problems that arise in the implementation of the CBT system are experiencing problems during the simultaneous login process, experiencing errors in the middle of working on the questions. To evaluate this system, a questionnaire was distributed to phase E/grade 10 students to find out the level of suitability of the CBT website on student satisfaction, the gap between the performance of the CBT website and student expectations, important attributes, and mapping improvement priorities. Then the results of the questionnaire were analyzed using the Servqual method, Gap Analysis, and the IPA Model. The results of the analysis show that the overall average conformity level of the CBT website is 87% included in the high satisfaction category based on the Steers criteria, the gap value is -0.56 even though based on the level of conformity it is already in the high satisfaction category but there is still a gap between the performance of the CBT website and expectations. students, seen from the Cartesian diagram of the IPA Model as many as 22 attributes that have been mapped to Quadrants A, B, C, and D, make improvements especially in Quadrant A which need to be prioritized namely infrastructure attributes, punctuality, fast and precise services, admin knowledge and trust, concern.